The Representation Of The United States In Mainstream English Newspapers Of Pakistan: An Analysis Of Political Cartoons (1991-2013) - Ashfaq, Ayesha (2014)

(untitled)
Realism has always been a driving force behind the foreign policies of the United States across the world. Therefore, the US interests in geo-strategic position of Pakistan always determine the fluctuating nature of the Pakistan-United States relations. Based on this ‗interest specific‘ relationship, the representation of the United States has become an interesting dimension of Pakistani political cartoonists. Realisme sentiasa menjadi daya penggerak kepada dasar-dasar Amerika Syarikat di seluruh dunia. Kecederungan Amerika Syarikat dalam kedudukan geo- strategik Pakistan telah mencorakkan turun naiknya perhubungan di antara Pakistan dan Amerika Syarikat (Pak-US). Berdasarkan kepada kecederungan perhubungan tertentu ini dalam pembinaan imej di Amerika Syarikat, ia telah menjadi dimensi tarikan kepada kartunis politik di Pakistan.